Fear of mating out (FOMO): voyeurism does not increase mating propensity in fruit flies - Regina Vega-Trejo; Krish Sanghvi; Biliana Todorova; Irem Sepil; Eleanor Bath (Scientific Reports)
Abstract Mate availability and social information can influence mating behaviour in both males and females. Social information obtained from conspecifics can influence mate choice, particularly shown by studies on mate choice copying. However, the role of directly observing conspecific mating on mating behaviour has been less explored. As such, whether conspecifics are copulating or not could inform ‘observers’ about the availability of mates, or even stimulate observers to mate themselves. Using Drosophila melanogaster, we tested whether exposure to the visual cue of a mating pair would increase the mating propensity of an observer pair (i.e., voyeur). We followed a factorial design where a male-female pair (voyeur flies) were placed together with or without visual access to another pair of flies (who were either mating or not mating). We found no evidence that mating latency or duration of mating were affected by whether voyeurs had visual access to a mating or non-mating pair. These results could be due to biological factors (e.g., use of other non-visual cues by flies to acquire information related to sex), or methodological limitations of our study (e.g., flies unable to watch other pairs). Generally, our results suggest that fruit flies do not use visual cues from conspecifics mating to adjust their own mating latency or mating duration.